Réflexions sur le sens et la portée au Québec des articles 25, 35, et 37 de la Loi constitutionnelle de 1982 - Emery, Georges (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
The rights of aboriginal peoples may vary from one part of the country to the other. This stems from the origin of Canada, its history, its Imperial and the Constitutional Statutes which have determined the territorial evolution of Canada. The terms of the Quebec Act seem to limit the hunting territories of the Indians to that part of Quebec which was not a part of the Colony in 1763. While a federal law extinguished all aboriginal rights in the territory covered by the James Bay agreements, the amendment of 16 March 1983 may have, for Quebec, important legal consequences in that these agreements may be held to be treaties.